Canadian Thoracic Society 2012 Guideline Update: Diagnosis and Management of Asthma in Preschoolers, Children and Adults: Executive Summary. Issue 6 (2012) - Lougheed, M Diane; Lemiere, Catherine; Ducharme, Francine M; Licskai, Chris; Dell, Sharon D; Rowe, Brian H; FitzGerald, Mark; Leigh, Richard; Watson, Wade; Boulet, Louis-Philippe; Canadian Thoracic Society Asthma Clinical Assembly,
Abstract : BACKGROUND: In 2010, the Canadian Thoracic Society (CTS) published a Consensus Summary for the diagnosis and management of asthma in children six years of age and older, and adults, including an updated Asthma Management Continuum. The CTS Asthma Clinical Assembly subsequently began a formal clinical practice guideline update process, focusing, in this first iteration, on topics of controversy and/or gaps in the previous guidelines. METHODS: Four clinical questions were identified as a focus for the updated guideline: the role of noninvasive measurements of airway inflammation for the adjustment of anti-inflammatory therapy; the initiation of adjunct therapy to inhaled corticosteroids (ICS) for uncontrolled asthma; the role of a single inhaler of an ICS/long-acting beta2 -agonist combination as a reliever, and as a reliever and a controller; and the escalation of controller medication for acute loss of asthma control as part of a self-management action plan. The expert panel followed an adaptation process to identify and appraise existing guidelines on the specified topics. In addition, literature searches were performed to identify relevant systematic reviews and randomized controlled trials. The panel formally assessed and graded the evidence, and made 34 recommendations. RESULTS: The updated guideline recommendations outline a role for inclusion of assessment of sputum eosinophils, in addition to standard measures of asthma control, to guide adjustment of controller therapy in adults with moderate to severe asthma. Appraisal of the evidence regarding which adjunct controller therapy to add to ICS and at what ICS dose to begin adjunct therapy in children and adults with poor asthma control supported the 2010 CTS Consensus Summary recommendations. New recommendations for the adjustment of controller medication within written action plans are provided. Finally, priority areas for future research were identified. CONCLUSIONS: The present document is an executive summary of the first update of the CTS Asthma Guidelines following the Canadian Respiratory Guidelines Committee's new guideline development process. Tools and strategies to support guideline implementation will be developed and the CTS will continue to regularly provide updates reflecting new evidence.